Preloading Model on Soft Soil with Inclusion Thermal Induction Vertical and Incline Types - Panjaitan, Maraden; Djamaluddin, A. R.; Harianto, Tri; Muhiddin, A. B. (Salehan Institute of Higher Education, 2021)
Soft clay has a relatively low subgrade bearing capacity. The aim is to obtain physical values, mineralogy, mechanical strength values, values for reduction. The research method used is preloading in a test tube measuring 50×70×150 cm. Each cycle of preloading and thermal induction used a fixed load of 0.015 kg/cm². Thermal induction is given vertically and obliquely with temperature variations of 100, 200, 300, and 400 °C. The main observation point is a distance of 15 cm from the center of the induction. At 400 °C inclined induction, the water content is 17.36% (from the initial water content of 59.07%), the soil cohesion is 21.75. kN/m², the value of unconfined compressive strength is 67.72 kN/m², the highest modulus of elasticity is 4593 kN/m2, and the decrease is 5.13 cm. XRD, SEM, EDS results before heating showed mineralogy 0 (65.06%), Ca (13.30%), Na (3.64%), Mg (2.15%), Al (6.63%), Si (8.52%), Sn (0.70%) and did not change significantly after heating at 400 °C. The results after heating included 0 (58.39%), Ca (14.09%), Na (0.72%), Mg (1.16%), Al (6.63%), Si (14.72%), Sn (2.54%). The novelty obtained is to change very soft conditions became medium conditions. Doi: 10.28991/cej-2021-03091705 Full Text: PDF